Jual Beli Online Perspektif Hukum Islam dan Implikasinya Terhadap Pembangunan Karakter - Azi Ramdani; Aini Ali Agustin; Nendi Sahrul Mujahid; Deca Deca; Fitri Syifa Nuriyah; Nova Merisa; Arlan Hidayatulloh (Jurnal Ilmiah Wahana Pendidikan, 2022)
Buying and selling online or through internet facilities today is increasingly becoming a very popular buying and selling model as a result of the development of information and communication technology. The research method used is library research. The results of the study show that the salam contract is an order contract by paying first and the goods are delivered later, but the characteristics of the goods must be clear. In Islam it is required to be clearer in providing a legal basis, therefore Islam attaches a legal basis attached to the Qur'an, al-Hadith or ijma. It should be noted that prior to knowing this transaction specifically in the Qur'an, nothing that has been used as a legal basis is a global sale and purchase transaction, because bai' as-salam is one of the special forms of buying and selling, so the hadith of the Prophet and ijma' scholars explain a lot and of course the Qur'an which talks about globally already includes the permissibility of the sale and purchase of salam. therefore Islam attaches a legal basis attached to the Qur'an, al-Hadith or ijma. The implication of buying and selling online for character building is as an exercise of honesty and instilling a trusting attitude towards buyers and sellers. So with its online presence as a form of test as well as an evaluation of honest and trustworthy behavior in conducting transactions.